The Utilization of Youtube in Learning Mathematics Based on Study Level: Systematic Literature Review - Dina Zhafira (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
Learning mathematics in the era of e-learning system is challenging. Due to the era of massive technology and social media we need to adapt the learning process. One of the ways is by using one of social media that can help student to learning mathematics, youtube. This study aims to analyze the utilization of youtube in learning mathematics based on study level from elementary school, junior high school, senior high school and higher education. The research method used is Systematic Literature Review (SLR). The sample comprises 18 research results on the utilization of youtube in learning mathematics. The key research question is how is the utilization of youtube in learning mathematics based on level of study. The SLR method found that it has a linear relation between the utilization of youtube in learning mathematics with the positive impact that youtube bring in the learning process in each level of study. It shown us the utilization of youtube in learning mathematics has positive impact and influence the learning mathematics competence, interest, motivation and outcomes. However, the utilization of youtube also can be less impactful if it is used unproperly. So that, we need to maintain the purpose of youtube due to the process of learning mathematics.